Clarithromycin, trimethoprim, and penicillin and oxidative nucleic acid modifications in humans: randomised, controlled trials - Larsen, Emil List (Br J Clin Pharmacol, 2017)
AIMS: In vitro studies have demonstrated that formation of reactive oxygen species (ROS) contributes to the effect of bactericidal antibiotics. The formation of ROS is not restricted to bacteria, but also occurs in mammalian cells. Oxidative stress is linked to several diseases. This study investigates whether antibiotic drugs induce oxidative stress in healthy humans as a possible mechanism for adverse reactions to the antibiotic drugs. METHODS: This study contains information from two randomised, controlled trials. Participants underwent 1 week treatment with clarithromycin, trimethoprim, phenoxymethylpenicillin (penicillin V), or placebo. Oxidative modifications were measured as 24‐h urinary excretion of 8‐oxo‐7,8‐dihydro‐2′‐deoxyguanosine (8‐oxodG) and 8‐oxo‐7,8‐dihydroguanosine (8‐oxoGuo), and plasma levels of malondialdehyde before and after treatment as a measurement of DNA oxidation, RNA oxidation, and lipid peroxidation, respectively. RESULTS: Clarithromycin significantly increased urinary excretion of 8‐oxodG by 22.0% (95% confidence interval (CI): 3.6–40.4%) and 8‐oxoGuo by 14.9% (95% CI: 3.7–26.1%). Further, we demonstrated that trimethoprim significantly lowered urinary excretion of 8‐oxodG by 21.7% (95% CI: 5.8–37.6%), but did not influence urinary excretion of 8‐oxoGuo. Penicillin V did not influence urinary excretion of 8‐oxodG or 8‐oxoGuo. None of the antibiotic drugs influenced plasma levels of malondialdehyde. CONCLUSION: Clarithromycin significantly increases oxidative nucleic acid modifications. Increased oxidative modifications might explain some of clarithromycin's known adverse reactions. Trimethoprim significantly lowers DNA oxidation but not RNA oxidation. Penicillin V had no effect on oxidative nucleic acid modifications.